Llàtzer Gracia, a committed playwright - Gallén , Enric (Talía. Revista de estudios teatrales, 2025)
Llàtzer Garcia, playwright and director, he began his professional career in 2010 in Catalan theatre with an original, personal project, socially committed, and focused on immediate reality. Between comedy and drama, he has also adapted foreign contemporary narrative and theatre writers. Garcia prioritizes a theatre that deals with current problems of common interest to all, absolutely contrary to the idea of a cryptic theatre.